Rancang Bangun Aplikasi E-Letter Berbasis Web pada Unit Pelayanan Pemungutan Pajak Daerah Kecamatan Koja, Jakarta Utara - Pradana, Muhammad Bagas (Universitas Negeri Jakarta, 2022)
Letters within the scope of the regional tax office are used as intermediaries to follow up on requests from taxpayers. Unit Pelayanan Pemungutan Pajak Daerah Kecamatan Koja, Jakarta Utara is an official tribe formed by the Badan Pendapatan Daerah (BAPENDA) DKI Jakarta Provincial, where the UPPPD Kecamatan Koja is tasked with carrying out regional tax revenue service activities, especially in the Kecamatan Koja, Jakarta Utara. The challenge faced by UPPPD Kecamatan Koja is when the number of applications received is calculated to be more than it can handle. Within one day UPPPD Kecamatan Koja can receive 20-50 requests from taxpayers. Each request will be made with an Inspection Report (LHP) which requires an average time of 12 minutes for one LHP. The cause of making this LHP takes a long time because there is a lot of data redundancy during LHP manufacture. This problem has been going on for nine years. In this thesis, the researcher tries to provide a solution to these problems by designing a web-based application that can speed up the creation of an Examination Result Report (LHP). This application was developed using the SDLC software development method with a Prototype Model, the PHP programming language, the Bootstrap framework for the front-end, and the MySQL database. At the end of the development, testing was carried out using UAT (User Acceptance Test) both functionally and usefully, it can be said that the Web-Based E-Letter Application design at Unit Pelayanan Pemungutan Pajak Daerah Kecamatan Koja, Jakarta Utara, has been going well and as expected with a usability rate of 91.50% on the whole system